Zero Tolerance for Bullying: Effective Measures to Stop and Prevent Harassment in Schools - Irsyadiah, Nur; Syahrullah, Syahrullah; Atmowidjoyo, Sutardjo; Khasanah, Siti Uswatun (EDUTEC : Journal of Education And Technology, 2024)
Bullying of students is a problem that is widespread in Jakarta. This bullying is caused by several factors such as parenting patterns, school, self-esteem and group norms. The aim of this research is to socialize to stop and prevent bullying at Sejahtera Vocational School. The research method uses quantitative descriptive to describe the conditions that occurred during the research. The focus of the research was Sejahtera Pare Vocational School, Kerdiri Regency, East Java with 40 students as respondents. Sampling was carried out through random sampling and data collection using a questionnaire as a tool. Quantitative Research Methods are used to research certain populations or samples. The data analysis technique uses frequency distribution. Research results Based on the analysis of the results and discussion, it can be concluded that the bullying that occurred at Sejahtera Pare Vocational School, Kadiri Regency, East Java, when viewed as a whole, is in the moderate category. This means that bullying at Sejahtera Pare Vocational School, Kediri Regency, East Java needs to be watched out for so that it can be minimized as much as possible.